APPARENT DIGESTIBILITY OF FISH MEAL, BLOOD MEAL AND MEAT MEAL FOR LABEO ROHITA FINGERLINGS - S. M. Hussain; M. Afzal; M. Salim; A. Javid; T. A. A. Khichi; M. Hussain; S. A. Raza (Journal of Animal and Plant Sciences, 2011)
A feeding trial was conducted to determine the apparent nutrient digestibility of three feed ingredients of animal protein sources for Labeo rohita fingerlings. Reference diet was mixed with test ingredients in 70:30 ratios to formulate test diets. Chromic oxide was added as an indigestible marker. Apparent nutrient digestibility coefficient of dry matter and crude fat for blood meal and fish meal was significantly higher than meat meal at P<0.05. The crude protein digestibility values of blood meal (71.90±1.98) were significantly lower than fish meal (80.20±1.27) and meat meal (79.92±2.40). The apparent gross energy digestibility of fish meal (69.30±3.71) was significantly higher from meat meal (61.55±4.63) and blood meal (59.55±5.20). The nutrient digestibility values of fish meal and blood meal for dry matter and crude fat are similar whereas for crude protein the digestibility values of fish meal and meat meal are close to each other. It is concluded from this study that blood meal and meat meal can be included in diets of Labeo rohita fingerlings.
Keywords: Nutrient digestibility; Labeo rohita; Fish meal; Blood meal; Meat meal